DIGITAL MARKETING AND PRODUCT QUALITY ON CONSUMER LOYALTY OF EMBROIDERY AND EMBROIDERY PRODUCTS - Rina Susanti; Deni Amelia (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2022)
This study intends to examine the mediating effect of consumer satisfaction on the influence of digital marketing and product quality on consumer loyalty. We distributed 100 questionnaires and all of them were returned and usable. The hypothesis was tested using Partial Least Squares Structural Equation Modeling (PLS-SEM) which managed to reveal that digital marketing and product quality have a positive and significant effect on customer satisfaction; digital marketing, product quality and customer satisfaction have a positive and significant effect on customer satisfaction. These findings illustrate that consumer satisfaction has a positive and significant mediating effect on the effect of digital marketing and product quality on consumer loyalty. This study intends to identify consumer loyalty and its determinants in UMKM actors in Bukittinggi. This is because there were only a few previous studies on embroidery and embroidery UMKM actors Therefore, this study offers a theoretical basis for further studies and practical implications for business actors